Modifiable lifestyle risk factors and C-reactive protein in patients with coronary artery disease: Implications for an anti-inflammatory treatment target population. (10th November 2019) - Blaum, Christopher; Brunner, Fabian J; Kröger, Friederike; Braetz, Julian; Lorenz, Thiess; Goßling, Alina; Ojeda, Francisco; Koester, Lukas; Karakas, Mahir; Zeller, Tanja; Westermann, Dirk; Schnabel, Renate; et al.
Abstract: Background: Modifiable lifestyle risk factors (modRF) of coronary artery disease (CAD) are associated with increased inflammation represented by elevated C-reactive protein (CRP) levels. Lifestyle changes may influence the inflammatory burden in patients with CAD, relevantly modifying the target population for emerging anti-inflammatory compounds. Aims: The aims of this study were to analyse the association of modRF and CRP levels in CAD patients, and to define a potential target population for anti-inflammatory treatment with and without the optimisation of modRF. Methods: We included all patients with angiographically documented CAD from the observational cohort study INTERCATH. Patients with recent myocardial infarction, malignancy, infectious disease, and pre-existing immunosuppressive medication including a history of solid organ transplantation were excluded. Overweight (body mass index (BMI) ≥ 25 kg/m 2 ), smoking, lack of physical activity (PA; <1.5 h/week), and poor diet (≤12 points of an established Mediterranean diet score (MDS), range 0–28 points) were considered as modRF. CRP was measured by a high-sensitivity assay (hsCRP) at baseline. We performed multivariable linear regressions with log-transformed hsCRP as the dependent variable. Based on these associations, we calculated potential hsCRP levels for each patient, assuming optimisation of the individual modRF. Results: Of 1014 patients, 737 (73%) were male, the mean age was 69 years, and 483 (48%) had an hsCRP ≥ 2 mg/l. ModRF were significantly overrepresented in patients with hsCRP ≥ 2 mg/l compared to patients with an hsCRP < 2 mg/l (BMI ≥ 25 kg/m 2 : 76% vs 61%; PA < 1.5 h/week: 69% vs 57%; MDS ≤ 12: 46% vs 37%; smoking: 61% vs 54%; p < 0.05 for all). hsCRP increased with the incremental number of modRF present (median hsCRP values for N = 0, 1, 2, 3, and 4 modRF: 1.1, 1.0, 1.6, 2.4, 2.8 mg/l, p < 0.001). Multivariable linear regression adjusting for age, sex, intake of lipid-lowering medication, and diabetes mellitus revealed independent associations between log-transformed hsCRP and all modRF (BMI ≥ 25 kg/m 2 : exp(ß) = 1.55, p < 0.001; PA < 1.5 h/week: exp(ß) = 1.33, p < 0.001; MDS ≤ 12: exp(ß) = 1.18, p = 0.018; smoking: exp(ß) = 1.18, p = 0.019). Individual recalculation of hsCRP levels assuming optimisation of modRF identified 183 out of 483 (38%) patients with hsCRP ≥ 2 mg/l who could achieve an hsCRP < 2 mg/l via lifestyle changes. Conclusion: modRF are strongly and independently associated with CRP levels in patients with CAD. A relevant portion of CAD patients with high inflammatory burden could achieve an hsCRP < 2 mg/l by lifestyle changes alone. This should be considered both in view of the cost and side-effects of pharmacological anti-inflammatory treatment and for the design of future clinical trials in this field.